The research of establishing discriminant function for patients with angina pectoris by stepwise analysis based on serum inflammatory factors - Chen, Zhi-bin (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2012)
OBJECTIVE: To improve cost-efficiency, discriminant functions in stepwise method was founded for the differential diagnosis of angina pectoris by detecting the serum level of high-sensitivity C-reactive protein (hs-CRP), macrophage migration inhibitory factor (MIF), interleukin-4 (IL-4) and interleukin-10 (IL-10) in patients with stable angina pectoris (SAP) and unstable angina pectoris (UAP)